Effect of "living high-training low" on the cardiac functions at sea level - Liu, Y.; Steinacker, J. M.; Dehnert, C.; Menold, E.; Baur, S.; Lormes, W.; Lehmann, M. (International Journal of Sports Medicine, 1998)
Living high-training low (LHTL), living at high altitude and training at sea level, is reported to be beneficial in enhancing physical performance. Effect of LHTL on cardiac function which is one of major determinants in performance, however, was not examined. To address this issue, 21 well-trained triathletes divided into control (n = 10, living and training at sea level) and LHTL group (living at 1980 m altitude > or = 12 hrs/day and training at sea level) were Doppler echocardiographically examined before and at the end of the two-week program. Heart rate and blood pressure did not change in both groups. At end of the training, left ventricular endsystolic diameter of LHTL group was smaller than that of controls (32 vs 34 mm, P < 0.05). Shortening fraction and ejection fraction in LHTL group increased by 9% and 17 %, respectively, P < 0.05. Preejection period/ejection time was more greatly reduced in LHTL group (P < 0.05). Stroke volume and cardiac output in LHTL increased. Diastolic function was not significantly affected by LHTL. These results suggest that LHTL produced an improvement of systolic function underlined by incremented left ventricular contractility, which might be associated with increased beta-adrenergic receptor or an improved myocardial energy utilization.